On electrical analysis of Al-rich p-AlGaN films for III-nitride UV light emitters. (26th November 2021) - Jadhav, Aakash; Bagheri, Pegah; Klump, Andrew; Khachariya, Dolar; Mita, Seiji; Reddy, Pramod; Rathkanthiwar, Shashwat; Kirste, Ronny; Collazo, Ramon; Sitar, Zlatko; Sarkar, Biplab
Abstract: In this work, an alternative scheme to estimate the resistivity and ionization energy of Al-rich p-AlGaN epitaxial films is developed using two large-area ohmic contacts. Accordingly, the resistivities measured using current–voltage measurements were observed to corroborate the Hall measurements in the Van der Pauw configuration. A free hole concentration of ∼1.5 × 10 17 cm −3 and low ionization energy of ∼65 meV in Mg-doped Al0.7 Ga0.3 N films is demonstrated. Nearly an order of magnitude lower hydrogen concentration than Mg in the as-grown AlGaN films is thought to reduce the Mg passivation and enable higher hole concentrations in Al-rich p-AlGaN films, compared to p-GaN films. The alternate methodology proposed in this work is expected to provide a simpler pathway to evaluate the electrical characteristics of Al-rich p-AlGaN films for future III-nitride ultraviolet light emitters.